2010
DOI: 10.2165/11203670-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Spotlight on Atomoxetine in Attention-Deficit Hyperactivity Disorder in Children and Adolescents†

Abstract: Atomoxetine (Strattera) is a selective noradrenaline (norepinephrine) reuptake inhibitor that is not classified as a stimulant, and is indicated for use in patients with attention-deficit hyperactivity disorder (ADHD). Atomoxetine is effective and generally well tolerated. It is significantly more effective than placebo and standard current therapy and does not differ significantly from, or is noninferior to, immediate-release methylphenidate; however, it is significantly less effective than the extended-relea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
119
1
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(130 citation statements)
references
References 47 publications
(75 reference statements)
6
119
1
4
Order By: Relevance
“…In a current review, which investigated the ATX treatment, it was concluded that ATX was significantly less effective than OROS-MPH and other extended-release mixed amphetamine salts. However, in this report, ATX was found non-inferior to IR-MPH regarding efficacy [18]. A recent study indicated that the balance of benefits and risks of ATX in the treatment of ADHD was positive [19].…”
Section: Discussioncontrasting
confidence: 60%
“…In a current review, which investigated the ATX treatment, it was concluded that ATX was significantly less effective than OROS-MPH and other extended-release mixed amphetamine salts. However, in this report, ATX was found non-inferior to IR-MPH regarding efficacy [18]. A recent study indicated that the balance of benefits and risks of ATX in the treatment of ADHD was positive [19].…”
Section: Discussioncontrasting
confidence: 60%
“…For example, immediate-release methylphenidate demonstrates similar efficacy to atomoxetine, but when comparing Concerta to atomoxetine, a clear advantage is observed with Concerta. 39 As of 2013, only 1 small pilot study formally evaluated using atomoxetine with methylphenidate. Although the pilot study had promising results, this combination cannot be recommended at this time owing to the limited amount of data available.…”
Section: Atomoxetinementioning
confidence: 99%
“…Atomoxetine is considered to be particularly beneficial as an adjunct therapy in ADHD patients presenting tics and comorbid anxiety (14)(15)(16). As it is devoid of abuse potential, atomoxetine is regarded as an appropriate alternative to the drugs that are misused (17).…”
Section: Discussionmentioning
confidence: 99%